(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Purpose: To identify syncretic elements derived from Christian influence in Central Asian Muslim traditions and to analyze their manifestations in contemporary religious practice. Methods: A qualitative study was conducted between 2021 and 2023 in five regions of Uzbekistan, Kyrgyzstan, Tajikistan, Turkmenistan, and Kazakhstan, with the participation of 166 respondents; in-depth interviews, focus group discussions, observation, and analysis of historical documents were employed. Results: 71.7% of respondents reported regularly or occasionally engaging in at least one syncretic practice. Shrine visitation (68.7%), forty-day ceremonies (84.3%), and recourse to sacred springs (52.4%) were identified as the most widespread elements. Conclusion: Syncretic elements assimilated from Christian, Zoroastrian, and Buddhist traditions have historically been integrated into Central Asian Muslim religious practice and remain actively present today, reflecting the complex, multi-layered nature of religious identity.